Irrationality: a history of the dark side of reason - Smith, Justin E. H. (Princeton University Press, 2020)
Cover -- Title -- Copyright -- Dedication -- CONTENTS -- Preface -- Preamble. A Mathematician's Murder -- Introduction -- Reason's Twin -- Enlightenment into Myth -- The Present Moment -- Irrationality: A Road Map -- CHAPTER ONE. The Self-Devouring Octopus -- or, Logic -- The Operation of Falsity -- Explosions -- Kaspar Hauser and the Limits of Rational Choice -- Carrying On about the Ineffable -- CHAPTER TWO. "No-Brainers" -- or, Reason in Nature -- An Ordered Whole -- Brute Beasts -- An Imperfect Superpower -- Small Pain Points -- CHAPTER THREE. The Sleep of Reason -- or, Dreams -- Upon Awakening -- Breaking the Law -- Spirits, Vapors, Winds -- Hearing Voices -- Bitter Little Embryos -- Postscriptum Fabulosum -- CHAPTER FOUR. Dreams into Things -- or, Art -- Many Worlds -- Bleeding Out -- Genies, Genius, and Ingenium -- What Is Art? -- The Two Magisteria -- CHAPTER FIVE. "I believe because it is absurd" -- or, Pseudoscience -- The Stars Down to Earth -- Let a Hundred Flowers Bloom -- Alternative Facts, and Alternatives to Facts -- The Paranoid Style in the Twenty-First Century -- CHAPTER SIX. Enlightenment -- or, Myth -- Better the Light -- The World-Soul on Horseback -- Poetic History -- Enlightenment into Myth, Again -- Why Democracy? -- CHAPTER SEVEN. The Human Beast -- or, the Internet -- An Escargotic Commotion -- The Modern Shiva -- Nothing Human Is Alien -- More Gender Trouble -- An Age of Extremes -- CHAPTER EIGHT. Explosions -- or, Jokes and Lies -- Into Nothing -- Charlie Hebdo and After -- Pseudologia Generalis -- Croaking -- CHAPTER NINE. The Impossible Syllogism -- or, Death -- "In the long run we are all dead" -- Radical Choices -- Youth and Risk -- The Impossible Syllogism -- Tie Me Up -- Cargo Cults -- In Loving Repetition -- Conclusion -- Acknowledgments -- Notes -- Bibliography -- Index.